Sperva on khleshchet samogon... potom yego kidayet v son. pora, druz'ya, takikh, kak on, za shivorot - i s polya von! - Nedospasov, B. D; Starodubtsev, P
Tractor rolling over a bottle of vodka. Driver is watched by a raven. Original title: сперва он хлещет самогон... потом его кидает в сон. пора, друзья, таких, как он, за шиворот - и с поля вон! Suggested translation: First he whips moonshine ... Then he throws him to sleep. it's time friends like him for the scruff of the neck - and off the field! PO-2231